Analisis Kinerja Perusahaan Dimiliki Asing dan Dimiliki Dalam Negeri (Study Kasus Perusahaan Pertambangan Terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Suhatman; nasfi, nasfi (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2021)
The study aims to analyze the performance of foreign-owned companies and domestically-owned companies on financial performance with the object of research being 47 mining companies listed on the Indonesia Stock Exchange at the end of 2020. Based on the completeness of the data studied, only 11 companies were selected. sample from 2016 to 2020. The independent variables of this study are foreign-owned companies (X1) and domestically owned (X2). The dependent variable is financial performance (Y) consisting of NPM, ROA and ROE. Multiple linear regression data analysis using SPSS version 23. The results showed that foreign owned companies and domestically owned companies (domestic) had a significant effect on financial performance (NPM, ROA and ROE), then the test results simultaneously showed that foreign owned companies and foreign owned companies domestic (domestic) significant effect on financial performance. With the magnitude of the influence is only 56.4% while 43.6% is influenced by other factors.